Trans identités : genres pluriel.le.s : acceuil, droits, santé, jeunesse, emploi... tous.tes bien informé.e.s - Dufrasne, Aurore; Lucthiviste, Louis; Nisol, Max (Bruxelles : Genres Pluriels, 2020)
Fonds Suzan Daniel (FSD)
Frans
Brochure
Keywords: LGBTQ+; transgenderbeweging